Semiphysical Modelling of the Nonlinear Dynamics of a Surface Craft with LS-SVM. (4th December 2013) - Moreno-Salinas, David; Chaos, Dictino; Besada-Portas, Eva; López-Orozco, José Antonio; de la Cruz, Jesús M.; Aranda, Joaquín
Abstract : One of the most important problems in many research fields is the development of reliable mathematical models with good predictive ability to simulate experimental systems accurately. Moreover, in some of these fields, as marine systems, these models play a key role due to the changing environmental conditions and the complexity and high cost of the infrastructure needed to carry out experimental tests. In this paper, a semiphysical modelling technique based on least-squares support vector machines (LS-SVM) is proposed to determine a nonlinear mathematical model of a surface craft. The speed and steering equations of the nonlinear model of Blanke are determined analysing the rudder angle, surge and sway speeds, and yaw rate from real experimental data measured from a zig-zag manoeuvre made by a scale ship. The predictive ability of the model is tested with different manoeuvring experimental tests to show the good performance and prediction ability of the model computed.